Surrogate-model-based optimization of a nonideal polymerization reactor for producing tailored molecular weight distribution - Shin, Sunkyu; Lee, Won Bo; Park, Myung June (Chemical Engineering Journal, 2024)
The optimization of polymerization reactors with nonideal mixing has been greatly hindered by a tremendous computation burden. In this study, a global optimization framework to integrate full MWD calculations and detailed reactor dynamics with nonideal mixing behaviors was developed by reducing the considerable computation time required for implementing full MWD. A combination of surrogate-model-based optimization and a computational fluid dynamics (CFD)-compartment reactor model was applied to produce the desired MWD in a nonideal reactor. A neural network (NN) surrogate model was trained using 3,000 MWD data produced from the mechanistic reactor model. The results showed that the model successfully described asymmetric MWD with bimodality resulting from the nonideal mixing behaviors in the reactor. The surrogate model was used to construct operation maps for the asymmetry and bimodality factors, with SHapley Additive exPlanations (SHAP) values showing that the flow rate of the chain transfer agent had the largest impact on the asymmetry factor, whereas temperature significantly influenced the bimodality factor. Finally, the optimization strategy based on the asymmetric and bimodality factors successfully determined operating conditions to produce four tailored MWDs, reported in actual polymerization reactors with R scores of 0.988–0.997.
Keywords: Mixing behaviors; Model based optimization; Molecular-weight distributions; Neural-networks; Non-ideal mixing; Nonideal; Optimisations; Polymerization reactors; Reactor modelling; Surrogate modeling; Molecular weight distribution; Neural network; Nonideal mixing; Optimization; Surrogate model